Software Understandability using Software Metrics: An Exhaustive Review - Mohammad Saif Himayat; Dr. Jameel Ahmad (International Journal of Engineering and Management Research, 2023)
Stability and Understandability are two important aspects of software architecture quality measurement. Stability refers to the degree to which software architecture is resistant to change. A stable architecture is one that can accommodate changes with minimal impact on the overall system. In other words, a stable architecture is one that can evolve over time while maintaining its integrity. There are several metrics used to measure the stability of a software architecture, including the number of dependencies between components, the number of changes required to implement a new feature or fix a bug, and the amount of time it takes to make changes to the architecture. A stable architecture will have fewer dependencies between components, require fewer changes to implement new features or fix bugs, and make changes faster. Understandability refers to the degree to which a software architecture can be easily understood by developers and other stakeholders. An understandable architecture is one that is easy to navigate and comprehend, and that clearly communicates the system's design and functionality. There are several metrics used to measure the understandability of software architecture, including the number of components and their relationships, the level of abstraction used, and the degree of consistency between different parts of the architecture. An understandable architecture will have a clear structure and logical organization, use consistent terminology and notation, and be documented with clear explanations of its components and their relationships. a software architecture that is both stable and understandable will be easier to maintain, evolve, and extend over time, reducing the risk of errors and improving the overall quality of the system.